Automatização da técnica de empilhamento de ar: Análise da funcionalidade de um equipamento eletromédico - Araújo, Fabiana Lacerda de (2023)
The air stacking technique is widely indicated for patients who have some neuromuscular disease with restriction of pulmonary ventilation. It is performed with consecutive insufflations through a manual resuscitator. The scope of this research is to evaluate the functionality and compliance, through the current ABNT guidelines, of an electromedical equipment under study, characterized as a low cost home volumetric lung ventilator, based on the automation of the manual resuscitator in order to promote the maintenance of the lung ventilation and the volumetric increment in patients with neuromuscular diseases. This is an exploratory study with qualitative analysis. The research was carried out in partnership with the Laboratory of the Department of mechanical Engineering at UFPB, where the equipment was developed. The evaluation of the physical structure and functionality of the equipment will serve as a basis for improvements in the project development process, and the safety and performance tests will be of great importance to guarantee improvements and mitigate possible product failures, making it suitable for a future clinical trial.